2006
DOI: 10.1017/s0022112006001224
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds-number effects and anisotropy in transverse-jet mixing

Abstract: Experiments are described which measured concentration fields in liquid-phase strong transverse jets over the Reynolds-number range 1.0 × 10 3 6 Re j 6 20 × 10 3 . Laserinduced-fluorescence measurements were made of the jet-fluid-concentration fields at a jet-to-freestream velocity ratio of V r = 10. The concentration-field data for far-field (x/d j = 50) slices of the jet show that turbulent mixing in the transverse jet is Reynoldsnumber dependent over the range investigated, with a scalar-field PDF that evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 77 publications
0
49
0
Order By: Relevance
“…Note that these jet Reynolds numbers all substantially exceed the value of 10 3 beyond which the trajectory is insensitive to Reynolds number, following Shan and Dimotakis [26]. Buoyancy effects are negligible even at the lowest J value (J = 1.5), where the Froude number…”
Section: Experimental Facilitymentioning
confidence: 70%
See 1 more Smart Citation
“…Note that these jet Reynolds numbers all substantially exceed the value of 10 3 beyond which the trajectory is insensitive to Reynolds number, following Shan and Dimotakis [26]. Buoyancy effects are negligible even at the lowest J value (J = 1.5), where the Froude number…”
Section: Experimental Facilitymentioning
confidence: 70%
“…The coefficients, A and B, typically vary between the ranges 1.2 < A < 2.6 and 0.28 < B < 0.34, depending on such parameters as the velocity profile of the jet exit [24,25], the thickness of the boundary layer [24], and the specific definition used to identify the jet trajectory. Shan and Dimotakis [26] showed that jet trajectory is effectively independent of Reynolds number for 1.0 Â 10 3 6 Re d (tested up to Re d = 20.0 Â 10 3 ). The limited data for reacting jets indicates that the time-averaged jet trajectory is quite close to the nonreacting jet [27,28].…”
Section: Background: Time-averaged Jicf Flame Featuresmentioning
confidence: 99%
“…Another flow configuration that has been widely studied is the jet in crossflow [17,18]. The jet in crossflow has a higher entrainment rate than a jet into a quiescent reservoir, resulting in increased mixing [18].…”
Section: Introductionmentioning
confidence: 99%
“…The jet in crossflow has a higher entrainment rate than a jet into a quiescent reservoir, resulting in increased mixing [18]. For both free-shear layers and jets in crossflow, as the Reynolds number is increased, the strain rates experienced by a fluid element within the mixing zone will exceed the extinction strain rates of hydrocarbon fuels, for example, and result in flame-out with little recourse for reignition [19].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed overview of recent work on the current cross-flow stream can be found in [3]. Previous authors have investigated numerically the velocity field [4][5][6][7][8][9], and the passive scalar field of concentration considered in [10][11][12]. As well as numerical simulation of the velocity field were considered in papers [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%